Strategic versus Financial Investors: The Role of Strategic Objectives in Financial Contracting - Stefan Arping; Sonia Falconieri (Tinbergen Institute, 2009)
Strategic investors, such as corporate venture capitalists, engage in the financing of start-up firms to complement their core businesses and to facilitate the internalization of externalities. We argue that while strategic objectives make it more worthwhile for an investor to elicit high entrepreneurial effort, they can also undermine his commitment to penalize poorly performing entrepreneurs by terminating their projects. Based on this tradeoff we develop a theory of financing choice between strategic and financial investors. Our framework provides insights into the design of corporate venturing deals and the choice between corporate venturing and independent venture capital finance.
Keywords: G20; G24; G32; 330; Corporate Venturing; Soft Budget Constraint; Investition; Unternehmensfinanzierung; Risikokapital; Internalisierung externer Effekte; Liquiditätsbeschränkung